A two-phase gradual silver release mechanism from a nanostructured TiAlV surface as a possible antibacterial modification in implants - Pruchova, Eva; Kosova, Michaela; Fojt, Jaroslav; Jarolimova, Petra; Jablonska, Eva; Hybasek, Vojtech; Joska, Ludek (Bioelectrochemistry, 2019)
Titanium biomaterials are widely used in the medical field due to their biocompatibility and excellent corrosion and mechanical resistance. However, these materials have no antibacterial properties. To obtain an antibacterial active surface, a nanostructure of Ti6Al4V alloy was created. This specific nanostructure contained nanotubes and micro-cavities and was used as a substrate for silver anchoring. The electrochemical approach to silver reduction was studied. It is a common approach for silver deposition and in this work, inhomogeneities in the nanostructure were used as a preferential area for silver localisation. The galvanostatic regimen of deposition allowed for a technically quantitative process and the required silver placement. The experimental conditions used enabled testing and silver dissolution rate evaluation within a reasonable time span. Based on the corrosion and analytical results (EDS, XPS and ICP-MS), a two-phase silver release mechanism was confirmed. The openings of the individual nanotubes were filled with silver nanoparticles, whose release was relatively fast. By contrast, the silver anchored inside the cavities allowed the silver to release gradually. Antibacterial efficiency against Staphylococcus aureus and Escherichia coli was successfully demonstrated. Cytotoxicity testing with murine fibroblasts showed cell metabolic activity far above the normative limit of 70%.
Keywords: nanostruktury; Animals; Escherichia coli Infections; buněčné linie; infekce vyvolané Escherichia coli; biokompatibilní materiály; Escherichia coli; Prostheses and Implants; Silver; lidé; Titanium; Mice; Anti-Bacterial Agents; Drug Liberation; myši; titan; Cell Line; Staphylococcus aureus; Biocompatible Materials; stafylokokové infekce; Drug Delivery Systems; Staphylococcal Infections; protézy a implantáty; lékové transportní systémy; Nanostructures; zvířata; uvolňování léčiv; antibakteriální látky; stříbro; Humans